Herbage Production and Quality of Shrub Indigofera Treated by Different Concentration of Foliar Fertilizer - L Abdullah (Media Peternakan, 2010)
A field experiment on fodder legume Indigofera sp. was conducted to investigate the effects of foliar fertilizer concentration on forage yield and quality, and to identify optimum concentrations among the fertilizer treatments on herbage yield, chemical composition (CP, NDF, ADF, minerals), and in vitro dry matter (IVDMD) as wll as organic matter (IVOMD) digestibility in goat's rumen. Randomized block design was used for the six concentration of fertilizer treatments; control, 10, 20, 30, 40, and 50 g/10 l with 3 replicates. Leaves were sprayed with foliar fertilizer at 30, 34, 38, and 42 days after harvest. Samples were collected at 2 harvest times with 60 days cutting interval. Application of the foliar fertilizer up to 30 g/10 l significantly increased  herbage DM yield, twig numbers, tannin, saponin, Ca and P content, as well as herbage digestibility (IVDMD and IVOMD). The lower and higher concentration of foliar fertilizer resulted in lower value of those parameters, but NDF and ADF contents had the opposite patterns. The optimum level of foliar fertilizer that resulted the highest herbage yield and quality was 30 g/10 l, and the highest in vitro digestibility and Ca concentration was 20 g/10 l.